2011
DOI: 10.1158/1078-0432.ccr-11-0370
|View full text |Cite
|
Sign up to set email alerts
|

Dual Kinase Inhibition of EGFR and HER2 Overcomes Resistance to Cetuximab in a Novel In Vivo Model of Acquired Cetuximab Resistance

Abstract: Purpose Acquired resistance to cetuximab, a chimeric EGFR-targeting monoclonal antibody, is a widespread problem in the treatment of solid tumors. The paucity of preclinical models has limited investigations to determine the mechanism of acquired therapeutic resistance thereby limiting the development of effective treatments. The purpose of this study was to generate cetuximab-resistant tumors in vivo to characterize mechanisms of acquired resistance. Experimental Design We generated cetuximab-resistant clon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 38 publications
2
69
0
1
Order By: Relevance
“…45 ADC has become a powerful treatment strategy to overcome drug resistance like trastuzumab resistance. 35 The efficacy of PanP-DM1 on the cancer cells that are refractory to EGFR-directed antibodies will be explored in a future research publication.…”
Section: Discussionmentioning
confidence: 99%
“…45 ADC has become a powerful treatment strategy to overcome drug resistance like trastuzumab resistance. 35 The efficacy of PanP-DM1 on the cancer cells that are refractory to EGFR-directed antibodies will be explored in a future research publication.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hou et al (28) demonstrated a significant correlation between MAGE-A9 and -A11 expression and Her2/neu expression in breast cancer. There is a broad consensus that evasion of EGFR-targeted therapy is facilitated by the activation of alternative receptors, including Her2/neu, as well as their downstream signaling pathways (29,30). Even if TKI treatment combined with cisplatin and radiotherapy failed to improve progression-free survival in unselected cohorts, erlotinib and gefitinib may function as chemopreventive drugs (31).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR point mutations are not the only mechanism by which cancer cells are (or become) resistant to EGFR inhibitors. Activation of other RTKs such as ERBB2/ HER2 also occurs in cells resistant to cetuximab, an EGFR-targeting monoclonal antibody, which paves the way for the dual inhibition of both EGFR and HER2 to improve the clinical response [22]. Signaling from ERBB3/ HER3 is also specifically activated in epithelial malignancies treated with EGFR inhibitors [23][24][25].…”
Section: Box 1 Erbb Membersmentioning
confidence: 99%